Behavior Management Model and Business Plan Writing Problem of Enterprise Group and OTOP Entrepreneur in Chaiyaphum Province - Nakarin, Rassamepen; Mantra, Jeerawat; Phutcharinya, Annarviya; Nillabon, Phedetkiat (Journal for Developing the Social and Community, 2018)
The purposes of the research 1) to study the behaviors and the Business Plan of enterprise group and the OTOP Entrepreneur in Chaiyaphum province and 2) to analyze the problem and barriers factors affecting the Business Plan of enterprise group and the OTOP Entrepreneur in Chaiyaphum province in Chaiyaphum province. The mixed methodology between quantitative and qualitative research. The sample consists of OTOP Entrepreneur in Chaiyaphum province of 255 qualified as a sample of 10 member’s total of 265 samples. The statistics used purposive sampling in this study. The research findings were showed as follows : Most of the respondents were male, the 170 people were 66.67 percent and female’s 85 people were 33.33 percent. Most of Secondary Education 112 people, representing 43.92 per cent. Most other products, product categories, the number of 76 people 29.80 percent, followed by food and beverage, number 77 people representing 30.20 followed by food and beverage respectively. The behaviors and the Business Plan problems of Entrepreneur in Chaiyaphum province were clearly found in overall aspect at a moderate level. The problem and barriers : the aspect was found that the material, equipment, tools was the highest, followed by the process of the Business Plan and according to behavior, resulting in a business plan that is the motivation.